Reducing the number of microorganisms and organic carbon by implementation APS (Advanced Ponds System) in the wastewater of Dairy Goat with added liquid probiotics - Rendi Fathoni Hadi; Bayu Setya Hertanto; Ari Kusuwa Wati (Livestock and Animal Research, 2020)
Objective: The activities of the dairy goat group, in general, have not paid attention to the processing of livestock waste that comes from maintenance activities. For example, liquid waste from cleaning cages and livestock baths, dirt, urine, and milking activities. Dairy goat farm waste, if not appropriately managed can have a negative impact on the quality of underground water sources, surface water, and the surrounding environment. Application of the Advanced Ponds System (APS) system with at part of Algae Settling Ponds pool size of 3 m x 1.5 m x 1.5 m with a dose of 50 ml / m3 of probiotic liquid so that 337.5 ml was needed. This study aimed to improve the wastewater based on microbiological and psycochemical characteristics by treatment of advanced pond system with probiotic in dairy goat farm.Methods: The variables observed were the content of microorganisms (Escherichia coli and Salmonella sp.) and physicochemical characteristics (Total N, Organic matter, temperature, pH, organic carbon, C/N ratio) of dairy goat farm wastewater in the APS system at part of Algae Settling Ponds. Data were analyzed by independent samples t-test analysis.Results: The results showed that the addition of liquid probiotic had no significant effect on temperature, pH, and C / N ratio, but affected organic carbon, E. coli and Salmonella sp. (P<0.05).Conclusions: Based on the research results, it can be concluded the addition of liquid probiotic through the application of the Advanced Ponds System with at part of Algae Settling Ponds can be used as a solution to accelerate the improvement of the quality of dairy goat farm wastewater.